2021
DOI: 10.1364/osac.432084
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive photoacoustic screening of blood vasculature during anti-angiogenesis using CAM assay

Abstract: There is a strong need for non-invasive detection of normal tissue from diseased one and a better understanding of the factors involved in the infection’s growth. Continuous monitoring of tissue samples at different time points is highly desirable. We demonstrate using the photoacoustic spectral response technique (PASR) for in situ analysis in a developing chicken embryo as a model (CAM) for anti-angiogenesis and vascular development. The photoacoustic technique is an emerging modality that is based on the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The effect of the low-frequency region (0 to 1 MHz) and high-frequency region (1 to 10 MHz) at the spectral energy was investigated. The spectral energy at low-frequency region EL and high-frequency region EH was normalized with the Es, then resultant relative energies ELS and EHS were used to monitor the quantitative change at a specific frequency region, which can provide crucial information for tissue characterization 6 , 22 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of the low-frequency region (0 to 1 MHz) and high-frequency region (1 to 10 MHz) at the spectral energy was investigated. The spectral energy at low-frequency region EL and high-frequency region EH was normalized with the Es, then resultant relative energies ELS and EHS were used to monitor the quantitative change at a specific frequency region, which can provide crucial information for tissue characterization 6 , 22 …”
Section: Methodsmentioning
confidence: 99%
“…This theoretical understanding was both confirmed through an experimental investigation involving black rubber and validated via simulation studies, as depicted in Refs. 22 and 23 . These simulation studies revealed that an increase in density leads to a corresponding rise in sound speed, thereby causing a shift in the frequency spectra toward the higher frequency range.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The window is closed and retaped, the eggs were placed back into the incubator to allow the vasculature and growth for 5 to 7 days. After the incubation period the reduction in the growth of the veins were recorded and the inhibition of angiogenesis measured (12).…”
Section: Anti-angiogenic Activity Of Synthetic Ampmentioning
confidence: 99%
“…[22][23][24] Yet, it is crucial to note that spectral parameters contain valuable mechano-biological information that can be extracted. By harnessing this information, the technique can not only serve as a screening tool but also provide vital insights from a diagnostic perspective [24][25][26] in a costeffective manner. For instance, the relaxation time of the PA time-domain signal is associated with the elasticity of the sample.…”
Section: Introductionmentioning
confidence: 99%